Manipulating Single‐Photon Emission from Point Defects in Diamond and Silicon Carbide. Issue 7 (24th May 2021) - Bathen, Marianne Etzelmüller; Vines, Lasse
Abstract: Point defects in semiconductors are emerging as an important contender platform for quantum technology (QT) applications, showing potential for quantum computing, communication, and sensing. Indeed, point defects have been employed as nuclear spins for nanoscale sensing and memory in quantum registers, localized electron spins for quantum bits, and emitters of single photons in quantum communication and cryptography. However, to utilize point defects in semiconductors as single‐photon sources for QT, control over the influence of the surrounding environment on the emission process must be first established. Recent works have revealed strong manipulation of emission energies and intensities via coupling of point defect wavefunctions to external factors such as electric fields, strain and photonic devices. This review presents the state‐of‐the‐art on manipulation, tuning, and control of single‐photon emission from point defects focusing on two leading semiconductor materials—diamond and silicon carbide. Abstract : Quantum technology promises novel functionalities such as nanoscale sensing and secure communication, for which high‐quality single‐photon emitters (SPEs) are essential. Point defects in semiconductors are a contending platform, combining bright and room temperature SPEs with mature fabrication strategies. In this review, the authors summarize recent progress on controlling and manipulating SPEs from point defects in silicon carbide and diamond.